PENGARUH PERUBAHAN BI RATE MENJADI BI 7 DAY REVERSE REPO RATE TERHADAP JUMLAH KREDIT UMKM - Tia Ichwani; Ratna Sari Dewi (Jurnal Manajemen dan Bisnis, 2021)
Our research is aimed to find out the implementation of the new policy that Bank Indonesia sets regarding the change of BI Rate reference rate to BI 7 Days Reserve Repo Rate and its effect on UMKM’s credit in Indonesia. This research is a quantitative research using time series data and the method used is simple linear regression method using SPSS. Based on the results of this study indicates that there is a difference between the number of  UMKM’s credit, ie increasing the number of UMKM credit, when the BI 7 Day Reverse Repo Rate is enacted. The researcher hopes that Bank Indonesia will focus more on the determination of BI 7 Days REPO, because the policy has an effect on the number of UMKM credit and is expected to increase the state treasury.